Comparison of binocular visual function among patients with different types of anisometropia - Li Tang; Lei Li; Chunmei Li; Yulin Yu; Nan Shu; Li Zhang (Advances in Ophthalmology Practice and Research, 2025)
Objective: To compare the perceived eye position, Titmus and stereopsis function across various types of anisometropia to identify differences in binocular visual function. Methods: This study included 204 anisometropic patients (observation group, interocular spherical equivalent difference ≥1.5D or cylindrical ≥1.0D) and 57 non-anisometropic controls (interocular differences <1.5D spherical or <1.0D cylindrical). Participants were initially stratified based on documented amblyopia history (94 with vs. 110 without), followed by further subgrouping of the observation group into hyperopic, myopic, and astigmatic anisometropia types for comparative analysis with controls. Standardized assessments comprised best-corrected visual acuity (BCVA, logMAR), cycloplegic refraction, Titmus near stereopsis (arcsec), binocular perceptual eye position (PEP) deviation, and three-order stereopsis thresholds measured via a computerized binocular vision assessment system. Statistical analysis adhered to CONSORT guidelines (SPSS v26.0, α ​= ​0.05). Results: (1) No significant differences were observed between patients with documented amblyopia history and those without regarding equivalent spherical lens difference, horizontal/vertical PEP, three-order stereopsis, or Titmus test results. (2) The control group demonstrated superior vertical PEP, three-order stereopsis, and Titmus performance compared to all anisometropia subgroups (myopic, hypermetropic, and astigmatic; P ​<0.05), though horizontal PEP showed no significant variation (P ​>0.05). (3) While Titmus results showed no difference between astigmatic and myopic anisometropia groups (P ​= ​0.72), significant differences existed among other groups (P <0.05). Notably, the hyperopic anisometropia group exhibited the poorest normal rates for vertical PEP, Titmus, and three-order stereopsis among all groups (P ​<0.001). Additionally, the astigmatism group outperformed both myopia and hypermetropia groups in 0-order and 1-order stereopsis (P ​<0.05). Conclusions: The study revealed no significant difference in visual function between anisometropic amblyopia patients who achieved normal BCVA (≤0.0 LogMAR) and non-amblyopic anisometropic controls. However, all forms of anisometropia demonstrated varying degrees of impairment to binocular fusion and stereopsis, with hypermetropic anisometropia showing the most pronounced deficits, particularly in near stereopsis. Notably, vertical PEP instability may contribute to the progression of hyperopic anisometropia.